Effect of flame retardants on thermal stability and flammability of cured nitrile rubber - Rybiński, P.; Janowska, G. (Polimery, 2022)
Flammability of peroxide vulcanizates of acrylonitrile-butadiene rubber NBR 18, containing various flame retardants has been determined by thermal analysis (Table 1, Fig. 1-5). A clear relation between thermal decomposition rate of cured elastomer and its flammability, determined as oxygen index OI and combustion time in an air, was found (Table 2-7). The effects of particular flame retardants on the formation of a boundary layer (between a flame and a sample) and on the reactions in gas phase during combustion were discussed. The formation of liquid products of thermal decomposition during combustion of cured elastomer containing phosphoro-organic Disflamoll is the reason of easy combustion of these vulcanizates in an air. The most effective flame retardants appeared to be pentabromotoluene and mixtures of antimony oxide with chloroparaffin.